6. Chat and Instant Messaging Systems - Stein, Jennifer; Garber, Debbie; Baggaley, Jon (International Review of Research in Open and Distributed Learning, 2002)
Text-based conferencing can be both asynchronous (i.e., participants log into the conference at separate times), and synchronous (i.e., interaction takes place in real time). It is thus subject to the same wide variation as the online audio- and video-conferencing methods (see the earlier Reports in this series). Synchronous text-based approaches (e.g., online chat groups and instant messaging systems) are highly popular among online users generally owing to their ability to bring together special-interest groups from around the world without cost. In distance education (DE), however, synchronous chat methods are less widely used, owing in part to the problems of arranging for working adults in different time zones to join a discussion group simultaneously. Instant text messaging is more popular among DE users in view of the choice it provides between responding to a message immediately (synchronous communication) or after a delay (asynchronous). The different synchronous and asynchronous approaches are likely to become more widely used in parallel with one another, as they are integrated in individual product packages.The following comparison stresses the chat and instant messaging features of six integrated conferencing products.